Improving Security of the Crypto-Stego Approach using Time Sequence Dictionary and Spacing Modification Techniques - Harba , Eman S.; Harba, Hind S.; Abdulmunem, Inas Ali; Hussein, Samera Shams (Iraqi Journal of Science, 2021)
Cryptography steganography is a practical tool for data security. Hybridization of the cryptography with steganography can provide more security by taking advantage of each technique. This work proposes a method for improving the crypto-stego method by utilizing the proposed dictionary method to modified ciphertext. After that, the modified encrypt ciphertext id was hidden in the text by using the proposed method. For cryptography, an Advanced Encryption Standard (AES) was utilized to encrypt the message. The AES employed a 128bit block size and 256bit key size. The ciphertext characters were then replaced by the characters identified by a dictionary list. The dictionary is time-dependent, where each of the equivalent words shift based on the time-shift equation. The modified ciphertext was then embedded into a cover text so that the attacker cannot separate them by applying cryptanalysis. The "Modifying Spain" method used the "Space" to build a steganography tool that hides the secret message. The simulation results show that the proposed method achieved a high-security level when the cryptography and steganography are combined in such a way that the ciphertext is changed to another value by using a dictionary with a time sequence that makes the cryptanalysis test fails to guess and identify the algorithm that has been used for encryption. The stego test shows that the proposed method achieved good results in terms of capacity and visibility, being proved to be hard to notice. The tests also prove that the proposed method runs fast with less computational requirements.